Epistemologi Ibnu Khaldun dan Relevansinya Terhadap Kurikulum Pendidikan Agama Islam di Indonesia - Nurlaila, Sri Wisnu Nugraha; Rojab, Taufik Fahrul; Agustin, Usman (Undiksha, 2023)
This paper aims to reveal the epistemological concept offered by Ibnu Khaldun regarding Education and its relevance to the curriculum of Islamic Religious Education in Indonesia. The method used in this paper is descriptive qualitative analysis, by means of a literature study of documents and previous research texts, it is found that theoretically there is little relevance between the curriculum initiated by Ibnu Khaldun and the curriculum developed in Islamic Education in Indonesia, namely in in the field of classification, but there are differences in the fields of subjects that are developed fundamentally, Ibnu Khaldun emphasized that the existence of a scientific classification does not give rise to a scientific dichotomy between the naqqliyah and aqliyah